Analysing determinants of professional teacher competency attainment in pre-service teacher professional education - Sukarno; Suyud; Riyadini, Maria Vineki (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2025)
Among all educational resources, teacher professionalism significantly contributes to producing quality education graduates. Teachers stand at the forefront of the implementation of education in schools. As a dominant factor in the learning process, the quality of learning is strongly influenced by the quality of the teacher's performance in teaching. This study aims to identify determinant factors that determine the achievement of Teacher Professional Education (PPG) students' competencies to become professional teachers. This study reports the results of analyzing determinant factors as experienced teachers. The research design entails a quantitative survey study. A total of 288 respondents participated in the survey, comprising pre-service PPG students from several colleges in Yogyakarta and its environs. Survey results revealed determinant factors of professional teachers encompassing four dimensions: (1) teachers' attitudes towards teaching, (2) commitment to the teaching profession, (3) teachers' morale, and (4) teachers' work motivation. Emphasizing these dimensions in teacher education programs is vital for enhancing overall teaching quality.